Analysis of survival prognosis of degree of surgical treatment with targeted therapy for 224 cases of intermediate- and high- risk gastrointestinal stromal tumors patients - CUI Yi, HAN Zhen-guo (Jichu yixue yu linchuang, 2021)
Objective To explore the degree of radical surgery for patients with intermediate- and high-risk gastrointestinal stromal tumors (GIST) and to find the correlation between targeted drug therapy and survival prognosis, and then to summarize the clinical diagnosis and treatment experience. Methods A retrospective reciew of the complete pathological and follow-up data of intermediate and high risk GIST patients diagnosed by surgery and pathology in Shanxi Bethune Hospital from September 2012 to December 2019 was made, and the relevant factors that affect their prognosis. Results The patient's gender, age, tumor location, whether it was ruptured, the degree of radical surgery was summarized, targeted therapy, and the overall survival (OS) of 3 and 5 years were different(P＜0.05). The location of the primary tumor in GIST patients, whether the tumor was ruptured, the degree of radical surgery, and targeted therapy were independent prognostic factors that affected their 3-year and 5-year OS. There were differences in the prognosis of patients with different degrees of radical surgery, different risk grades, and whether to use targeted drug therapy(P＜0.05). Conclusions Complete surgical resection (R0) combined with targeted therapy is the main treatment to improve the prognosis of patients with intermediate- and high-risk GIST, but patients with intermediate-risk GIST who received targeted drug therapy after surgery are failed to significantly improve their overall survival.